1986
DOI: 10.1159/000124683
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stimulation of Anterior Pituitary Cell Cultures with CRF Leads to the Secretion of Lipotropin

Abstract: Time course studies have shown that the secretion of β-endorphin-related peptides from primary cultures of rat anterior pituitary reached a plateau after 1 h of stimulation by 10–7 Mcorticotropin-releasing factor (CRF); the major peptide released was β-endorphin 1–31. Further incubation of the cells with CRF led to a decline in the rate of secretion and to the appearance of a different pattern of peptides in which lipotropin was the principal component; analysis of the peptides remaining in the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…This is not surprising in light of the fact that the intracellular peptide content represents total peptide levels comprised of peptides con tained within heterogeneous secretory granules. It is pos sible that in some secretory granules, POMC undergoes only limited proteolysis, such that these granules contain PLPH as the primary end product [22], In other granules, POMC may be more extensively processed, such that PE is the primary end product [22], In addition, one type of granule may be more 'releasable' (that is, available for release) than the other, perhaps by virtue of its proximity to the plasma membrane. The mechanism(s) underlying the modulation by ILip and CRH of the secreted and/or intracellular proportions of pE relative to PLPH are not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising in light of the fact that the intracellular peptide content represents total peptide levels comprised of peptides con tained within heterogeneous secretory granules. It is pos sible that in some secretory granules, POMC undergoes only limited proteolysis, such that these granules contain PLPH as the primary end product [22], In other granules, POMC may be more extensively processed, such that PE is the primary end product [22], In addition, one type of granule may be more 'releasable' (that is, available for release) than the other, perhaps by virtue of its proximity to the plasma membrane. The mechanism(s) underlying the modulation by ILip and CRH of the secreted and/or intracellular proportions of pE relative to PLPH are not known.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mature end product is not necessarily that which is preferentially secreted upon corticotroph activation. Indeed, the type and duration of corticotroph stimulation have been demonstrated to alter dramatically the relative amounts of secreted pE and PLPH [22][23][24], Therefore, the generation, within a single cell, of several peptides possessing such a diverse array of biological activities necessitates the existence of an exqui sitely fine-tuned regulation of POMC gene expression and of POMC peptide processing, secretion and content. This suggests that the biochemical dynamics of the POMC molecule may be influenced by regulatory factors at sever al levels (transcriptional, translational and post-translational) and that different regulatory factors may be char acterized by distinct POMC modulatory profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Since the proteolytic cleav age of POMC follows an ordered sequence which occurs in a time-ordered manner [12], the increase in the time available for processing may allow the MSH-producing enzyme to split more MSH. A second explanation stems from our observation that CRF administration eliminated the presence of MSH in grafts, an effect which was not elicited by the intact pituitary since it was also observed in hypophysectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has, however, been shown that relatively minor changes in biochemical structure such as C-terminal trimming (12), a-amidation and a-Nacetylation (1 3) have profound effects on biological activity. There is now increasing evidence to suggest that, in addition to regulating POMC biosynthesis and release of POMC products, physiological regulators such as CRF and glucocorticoids may play a role in regulating the complex pattern of POMC processing (9,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme, plus increased carboxypeptidase activity (or a specific glucocorticoid-sensitive enzyme), may thus be crucial in the generation of NacaEP, the principal acetylated species produced in the abattoir/glucocorticoid-treated anterior pituitaries. Another possibility is the differential accumulation of the various POMC products in subpopulations of POMC-producing cells (19,20), which may be sensitive to different regulatory mechanisms (2 I), perhaps reflecting a heterogeneous distribution of releasable pools, as suggested by Ham and Smyth (9,14). The possibility also remains that these processing effects simply represent a change in intracellular steady state.…”
Section: Discussionmentioning
confidence: 99%